Free-ranging pigs identified as a multi-reservoir of Trypanosoma brucei and Trypanosoma congolense in the Vavoua area, a historical sleeping sickness focus of Côte d'Ivoire. - Barkissa Mélika Traoré; Mathurin Koffi; Martial Kassi N'Djetchi; Dramane Kaba; Jacques Kaboré; Hamidou Ilboudo; Bernadin Ahouty Ahouty; Minayégninrin Koné; Bamoro Coulibaly; Thomas Konan; Adeline Segard; Lingué Kouakou; et al. (Public Library of Science (PLoS), 2021)
Background The existence of an animal reservoir of Trypanosoma brucei gambiense (T. b. gambiense), the agent of human African trypanosomiasis (HAT), may compromise the interruption of transmission targeted by World Health Organization. The aim of this study was to investigate the presence of trypanosomes in pigs and people in the Vavoua HAT historical focus where cases were still diagnosed in the early 2010's. Methods For the human survey, we used the CATT, mini-anion exchange centrifugation technique and immune trypanolysis tests. For the animal survey, the buffy coat technique was also used as well as the PCR using Trypanosoma species specific, including the T. b. gambiense TgsGP detection using single round and nested PCRs, performed from animal blood samples and from strains isolated from subjects positive for parasitological investigations. Results No HAT cases were detected among 345 people tested. A total of 167 pigs were investigated. Free-ranging pigs appeared significantly more infected than pigs in pen. Over 70% of free-ranging pigs were positive for CATT and parasitological investigations and 27-43% were positive to trypanolysis depending on the antigen used. T. brucei was the most prevalent species (57%) followed by T. congolense (24%). Blood sample extracted DNA of T. brucei positive subjects were negative to single round TgsGP PCR. However, 1/22 and 6/22 isolated strains were positive with single round and nested TgsGP PCRs, respectively. Discussion Free-ranging pigs were identified as a multi-reservoir of T. brucei and/or T. congolense with mixed infections of different strains. This trypanosome diversity hinders the easy and direct detection of T. b. gambiense. We highlight the lack of tools to prove or exclude with certainty the presence of T. b. gambiense. This study once more highlights the need of technical improvements to explore the role of animals in the epidemiology of HAT.